Financial Planning in the Eyes of Traditional Store Owners at Mayestik Market Square, A Qualitative Study on market Potential - Fadhilah, Maryam; Iskandar, Budi Permadi (Journal of Business and Management, 2014)
Financial planning is a progressive and cumulative attainment of which is designed to accomplish, develop strategies in a financial goal or set of life and its circumstancesâ€¦â€. As in its term â€œfinanceâ€, financial planning is a product of financial services that has existed in Indonesia. In Indonesia, financial planning as a financial product is new and still in need of education. Educating market is needed because the user of this product is the party who are indeed in need of these services. The parties eligible for this service product are a party that has (1) a financial goal and (2) the financial capacity. Based on market conditions being seized by the financial planner, it can be seen that a segment of the market is still open and has not being touched by financial planners as the main target of their markets, namely middle-low income group and informal sector workers. It makes a group of traditional market storekeepers in Indonesia a group included into the market criteria that has not worked. The traditional market is a market that has a modest selling activity and where bargaining with the means of payment in the form of money is found (Dwi Utami, 2005). In order to fulfill the objectives of this research, a qualitative research with in-depth interview combined with observation are chosen. There are eighteen storekeepers, which has been interviewed as the object of this research. This research revealed the current characteristic of the storekeepers and its readiness to accept the financial planners presence. The findings is supported with the recommendation of the approach to marketing this financial product.Keywords: Financial Planner, Potential Market, and Traditional Market Storekeeper.